Inspiratory muscle fatigue significantly affects breathing frequency, stroke rate, and stroke length during 200-m front-crawl swimming - Lomax, M.; Castle, S. (The Journal of Strength and Conditioning Research, 2011)
The aim of the current study was to assess the impact of inspiratory muscle fatigue (IMF) on total breaths taken (ftot), breaths per minute (fb), stroke count (SC), stroke rate (SR), and stroke length (SL) during constant velocity front-crawl swimming. Eight collegiate swimmers undertook a 200-m front-crawl swim on 2 separate occasions. On 1 occasion, IMF was induced immediately before the swim (IMF trial), and on the other occasion, the swim was undertaken in the absence of IMF (control trial). Trials were administered using a randomized crossover design and at a swimming velocity equivalent to 85% of race pace: Pilot testing identified this as being the fastest pace, which did not induce IMF. Maximal inspiratory mouth pressure, which was measured at the mouth and from residual volume, fell by 17% (p < 0.05) in response to IMF but was unchanged in response to the swim itself (p < 0.05). When compared to the control trial, ftot, fb, SC, and SR increased (p < 0.05) and SL decreased (p < 0.05) in response to IMF. These data suggest that the increase in ftotand fb in the presence of IMF occurred, in part, in an attempt to alleviate dyspnea. As a result, SL decreased and SR and SC increased, although variability in the SR and SC response did occur. However, as a number of identical muscles are recruited during deep inspirations and the front-crawl arm stroke, the possibility that arm coordination was changed, in part, to compensate for a reduced force-generating capacity per arm stroke should not be overlooked.